The Impact of ERM and Institutional Ownership on Market Value Through ESG: Evidence from ASEAN Energy Firms - Wiji Astuti; Iin Rosini; Nofryanti (Universitas Negeri Semarang, 2026)
Purposes: This study aims to examine how enterprise risk management disclosure and institutional ownership influence market value performance on energy sector firms in ASEAN countries in 2021 until 2024, particularly in the context of in increasing global concerns about economic instability, climate change, sustainability and corporate governance. The research offers novelty by positioning ESG as both a direct signal and an indirect mediating mechanism in explaining firm value in emerg- ing markets. Methods: The research adopts a quantitative methodology and employs secondary data sourced from the annual reports of companies. The research sample was 25 companies in sector energy in Indonesia, Thailand, Malaysia, Singapore, and Philippine. The study adopts a non-random sampling technique, with purposive sampling used as the selection method. The Data analysis was carried out panel data regression by E-views 13, and the mediation effect undertaken by Sobel test. Findings: The results reveal that institutional ownership plays a significant role in influencing ESG and market value, while ESG is also found to significantly affect market value. In contrast, enterprise risk management does not have a substantial effect on either ESG or market value. The mediation analysis further reveals that ESG mediates the linkage between institutional ownership and market value, but does not mediate the linkage between ERM and market value. Novelty: This study contributes new insights by addressing gaps in previous research regarding the direct relationship between ERM, IO, ESG, and MVP. The study literature by conceptualizing ESG as an imperfect signalling mechanism in emerging markets, where its value relevance is not consist- ently recognized by investors. By focusing on the ASEAN energy sector characterized by heteroge- neous ESG practices and less mature market responses, thereby extending the current understand- ing of ESG’s role in market value. However, it has challenged to generalize the results of the findings generally according to the relatively small sample. Furthermore, the current research recommends increasing the sample to include companies in multiple sectors or geographies in order to further strengthen generalizations.